2016
DOI: 10.1007/s11239-016-1431-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of rapid measurement of Rivaroxaban plasma levels in patients with acute stroke

Abstract: Plasma levels of Rivaroxaban (RivLev) might be useful to guide therapeutic decisions in patients with acute stroke under Rivaroxaban. A prerequisite for the potential clinical usefulness is their rapid availability in emergency situations. Single-center explorative analysis from the Novel-Oral-Anticoagulants-in-Stroke-Patients-registry (NOACISP, cinicaltrials.gov:NCT02353585). We included consecutive patients with acute ischemic or hemorrhagic stroke under Rivaroxaban (last intake <48 h) in which RivLev determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 16 publications
0
34
0
1
Order By: Relevance
“…Our median TAT for inpatients was 1 hour 32 minutes with no significant difference between levels processed in or out of hours. Although this is slower than other real‐world studies, it is still clinically useful for most emergency and urgent situations. At our institution, urgent requests are flagged to laboratory staff by a combination of location of origin, for example the emergency department, and by telephone.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our median TAT for inpatients was 1 hour 32 minutes with no significant difference between levels processed in or out of hours. Although this is slower than other real‐world studies, it is still clinically useful for most emergency and urgent situations. At our institution, urgent requests are flagged to laboratory staff by a combination of location of origin, for example the emergency department, and by telephone.…”
Section: Discussionmentioning
confidence: 97%
“…The speed with which samples are processed from the point at which they arrive in the laboratory to a result being published is referred to as the turnaround time (TAT) . Few studies have assessed the TAT of DOAC levels but they demonstrate that they can be delivered in a time frame that is clinically relevant . For example, a recent study by Dincq et al achieved median TAT of 61 minutes and 67.6 minutes for apixaban and rivaroxaban respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of these tests is the preparation of plasma, which under ideal conditions takes approximately 35 minutes. 30 Moreover, standard coagulation tests have inadequacies when used to monitor DOACs due to significant variability in methodology and reagents used. 1,[31][32][33][34][35][36][37] Therefore, a coagulation test that can be procured and processed at the POC, provides a binary yes or no answer for the presence of DOAC anticoagulant effect, exhibits improved reliability and sensitivity over standard coagulation tests, and is cost effective would be of significant benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, details on the preanalytical and analytical processed used to achieve this TAT were not given. 9 The same team has also recently shown that determining rivaroxaban levels within a short TAT allowed thrombolysis for one-third of patients taking rivaroxaban who would otherwise be ineligible for this procedure. 10 Our real-life study confirms the possibility of reducing the TAT around 30 minutes for specific rivaroxaban and apixaban assays.…”
Section: Reduction Of the Turn-around Time For The Measurement Of Rivmentioning
confidence: 99%